Melatonin mitigates cadmium-induced oxidative damage and modulates polysaccharide biosynthesis in Bletilla striata - Niu, Deqiong; Dao, Zhonghai; Xiao, Zhifeng; Xiang, Ping; Zhou, Shiyong; Dong, Jinrun (Frontiers in Plant Science, 2025)
IntroductionCadmium (Cd), a highly toxic heavy metal, threatens ecosystems and human health. Bletilla striata (B. striata), a medicinal plant valued for its polysaccharide-rich rhizomes, exhibits significant tolerance to Cd stress. Melatonin (MT), a phytohormone, has emerged as a key regulator of plant resilience to heavy metal toxicity. However, the mechanisms underlying MT-mediated biosynthesis of B. striata polysaccharides (BSP) under Cd exposure, as well as its role in alleviating Cd-induced oxidative damage, remain poorly characterized.MethodsSoil was passivated with 250 μmol/L CdCl2·2.5H2O for one month before transplanting one-year-old B. striata seedlings. One week after transplantation, the leaves of B. striata were sprayed with MT (50, 100, and 200 μmol/L) weekly. After 60 days, samples were collected and analyzed for physiological and biochemical indices (chlorophyll, osmoregulatory substances, Cd, reactive oxygen species, antioxidant enzyme activities, polysaccharides, flavonoids and saponins). Additionally, samples from CK, Cd-only, and Cd+50MT groups were collected for integrated transcriptomic and metabolomic analyses, and the transcriptome data were validated via qRT-PCR.ResultsOur findings revealed that Cd stress substantially suppressed seedling growth, manifesting as significant reductions in fresh weight, dry weight, chlorophyll content, and proline accumulation relative to control plants. Under Cd stress, application of 50 μmol/L MT achieved the maximal reduction in the contents of hydrogen peroxide (H2O2) and malondialdehyde (MDA), while significantly enhancing the activities of antioxidant enzyme. Additionally, under the treatment of 50 μmol/L MT (Cd+50M), the contents of polysaccharides and flavonoids were also significantly increased. Multi-omics integration identified 21 differentially expressed genes (DEGs) and 4 differentially expressed metabolites (DEMs) prominently associated with the BSP biosynthetic pathway, among which 10 DEGs showed strong correlations with DEMs. Coexpression network analysis underscored MT-mediated modulation of pivotal BSP synthesis genes (e.g., FRK1, FRK3, FRK6, and HK2), with MYB, MYB-related, bHLH, and bZIP transcription factors implicated as central regulators. qRT-PCR analysis confirmed the reliability of the transcriptome data.DiscussionThis study is helpful for understanding the regulatory network of MT in BSP biosynthesis under Cd stress and the role of MT in alleviating Cd-induced oxidative damage, thereby providing potential strategies for cultivating medicinal plants in heavy metal-contaminated environments.